What food comforts you?: a retrospective analysis of dietary changes which occurred in the pandemic (Research, Society and Development, 2022)
The COVID-19 pandemic has increased interest in comfort foods. Several studies have demonstrated changes in the behavior and/or eating habits of the population in the search for a "comfortable" diet, that is, for foods capable of promoting well-being and comfort to individuals. Based on the highly heterogeneous concept of comfort foods, this research aimed to understand the dietary changes of the population and associate them with the search for comfort foods during the COVID-19 pandemic. This is a narrative review with systematic search for articles published from March 11, 2020 to December 31, 2021 in the PubMed, Web of Science and Embase databases, using descriptors combined with the help of Boolean operators: (COVID-19 OR Sars-CoV-2) AND (feeding behavior OR food habit* OR comfort food OR eating emotional). Twenty-three original articles were included, totaling 120,569 people evaluated, with a predominance of cross-sectional studies and adult population. Positive dietary changes were observed, such as: increased consumption of fruits, vegetables, increased access to the Mediterranean diet and increased consumption of homemade preparations, as well as negative ones: increase in the consumption of foods rich in sugars and/or fats, higher consumption of ultra-processed foods, fast snacks, snacks and industrialized food. According to the situational taxonomy of comfort foods described by Julie Locher (nostalgic foods, indulgence foods, convenience foods and physical comfort foods) and the highly idiosyncratic characteristics of this food category this review suggests that there may be a positive relationship between food changes resulting from the COVID-19 pandemic and the search for foods capable of promoting physical and/or emotional well-being to the individual.